Length-Weight Relation and Growth of Mangrove Crab - Sarton Thalib; Sitti Nursinar; Citra Panigoro (The NIKe Journal, 2019)
This study aims to determine the relation of length-weight and growth of mangrove crabs (Scylla serrata) in the Mootilango Village, Duhiadaa Sub-district, Pohuwato Regency. This research was conducted by observation for ± 6 months starting from September 2015 until February 2016. The sampling area covers all of Duhiadaa Sub-district mangrove forest with random sampling method. The result of the research shows that the relationship between carapace length and weight of mangrove crab (Scylla serrata) has the equation W = 6,026L2,444 with correlation (R2) = 0,850. Crab population consist of three age group (L1 = 61,66666667cm, L2 = 17,81981982, and L3 = 0,176691729 cm). While the maximum carapace length (L∞) reach 17.204 cm with a growth rate coefficient of 0.2133 per year. Keywords: length; weight; growth; mangrove crab; Scylla serrata